Implementasi Black Box Testing dan Acceptance Testing Fitur SKKM pada Cybercampus.uam.ac.id Universitas Anwar Medika - Kriswibowo, Rony; Prayogo, Johan Suryo; Febriana, Rusina Widha; Alia, Putri Ariatna (Jurnal Informatika Universitas Pamulang, 2023)
The Student Activity Credit System or abbreviated as (SKKM) recognizes and recognizes the existence of student activities in its development. However, Cybercampus still finds many errors with the SKKM feature, this can be seen from the fact that some students do not understand the SKKM feature. Students have difficulty inputting documents that must be uploaded, then there are some students who cannot access the SKKM feature. Based on existing problems, it is necessary to test applications to minimize functions that do not meet expectations. The scope of Testing is the system and based on the problem that many students do not understand the system, acceptance Testing is needed. Researchers tested the SKKM feature using Black Box Testing to identify which functions were damaged, interface errors, data structure errors, performance errors, initialization errors, and termination errors. Next, the second method uses the Acceptance test to test students' level of understanding and acceptance of the SKKM features on Cybercampus. The results of Black Box Testing showed that there were 12 test scenarios and 1 test scenario that was not suitable. Researchers provide recommendations for system improvements to improve system quality. then by using Acceptance Testing with 3 variables, namely Perceived Ease of Use, Perceived Usefulness, and Acceptance of IT. Then the conclusion from the overall Acceptance Testing was 75%. The conclusion of this research is that the features function as expected well and no major errors were found, so that the SKKM menu on cybercampus.uam.ac.id can be used immediately.